2021
DOI: 10.3390/fermentation7030122
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Microbial Hydrolysis Parameters of Poultry By-Products Using Probiotic Microorganisms to Obtain Protein Hydrolysates

Abstract: In connection with the active growth of poultry processing, the issue of rational use of poultry by-products is urgent. The paper proposes hydrolysis of the gizzards of broiler chickens and hens of the parent stock with bifidobacteria liquid concentrate (BLC) and Propionix liquid concentrated starter culture (Propionix LCSC). The effect of enzymatic treatment on changes in the structural components of the gizzards was studied using scanning electron microscopy (SEM) and determination of the dispersed compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
1
11
0
2
Order By: Relevance
“…The data obtained is consistent with the results of a previous study which found an increase in the content of free amino acids and the dispersion of hydrolysates during fermentation by microorganisms [26,30]. The presence of peptides with low-molecular weight in protein hydrolysates contributes to increases in water-holding and fat-holding capacities.…”
Section: Physicochemical and Technological Indicators Of Protein Hydr...supporting
confidence: 91%
See 2 more Smart Citations
“…The data obtained is consistent with the results of a previous study which found an increase in the content of free amino acids and the dispersion of hydrolysates during fermentation by microorganisms [26,30]. The presence of peptides with low-molecular weight in protein hydrolysates contributes to increases in water-holding and fat-holding capacities.…”
Section: Physicochemical and Technological Indicators Of Protein Hydr...supporting
confidence: 91%
“…Based on the results of previous studies and the optimal parameters of hydrolysis [26], the protein hydrolysate from the broiler chicken gizzards was obtained by means of microbial fermentation based on the technological scheme presented in Figure 1.…”
Section: Preparation Of Protein Hydrolysatementioning
confidence: 99%
See 1 more Smart Citation
“…By-product homogenates without added bacterial concentrates were taken as controls. All homogenates were fermented at 37 • C for 24 h. Optimization of the hydrolysis process is given in an earlier work [21].…”
Section: Biotechnological Processing Of By-product Samplesmentioning
confidence: 99%
“…Chicken processing generates a very large amount of waste, some of which contains a large amount of nutritional components. One such waste is chicken bone, which is largely unused or limited in the production of animal feed, pet food and fertilizer [9,10]. Chicken bones are not used properly despite their high nutritional value and protein content.…”
Section: Introductionmentioning
confidence: 99%